Does the updating of landslides inventories have a relevant impact on the landslide susceptibility assessment? - Melo, Raquel (2023)
Landslide inventories are essential for developing an accurate susceptibility assessment. However, the complete and systematic updating of these inventories is a time-consuming and challenging task. Therefore, we aimed to verify if the temporal updating of historical inventories improves the susceptibility models and if the size of the study area plays a relevant role in the decision to update or not landslide inventories. To answer these questions, the work was carried out in two study areas with different sizes but with a similar geomorphological context. The landslide susceptibility modelling, developed using the Information Value method, was performed for distinct types of landslides and using three landslide inventories: one with landslides that occurred before 2012; a second with landslides that occurred during the event of 2010; and a third with landslides that occurred up to 2019. The results indicate no improvement or only a residual enhancement in the susceptibility models’ predictive capacity, regardless of the type of landslide or the study area’s size.